The gut microbiome of the sea urchin, Lytechinus variegatus, from its natural habitat demonstrates selective attributes of microbial taxa and predictive metabolic profiles - Hakim, Joseph A. (FEMS Microbiol Ecol, 2016)
In this paper, we describe the microbial composition and their predictive metabolic profile in the sea urchin Lytechinus variegatus gut ecosystem along with samples from its habitat by using NextGen amplicon sequencing and downstream bioinformatics analyses. The microbial communities of the gut tissue revealed a near-exclusive abundance of Campylobacteraceae, whereas the pharynx tissue consisted of Tenericutes, followed by Gamma-, Alpha- and Epsilonproteobacteria at approximately equal capacities. The gut digesta and egested fecal pellets exhibited a microbial profile comprised of Gammaproteobacteria, mainly Vibrio, and Bacteroidetes. Both the seagrass and surrounding sea water revealed Alpha- and Betaproteobacteria. Bray–Curtis distances of microbial communities indicated a clustering profile with low intrasample variation. Predictive metagenomics performed on the microbial communities revealed that the gut tissue had high relative abundances of metabolisms assigned to the KEGG-Level-2 designation of energy metabolisms compared to the gut digesta, which had higher carbohydrate, amino acid and lipid metabolisms. Overall, the results of this study elaborate the spatial distribution of microbial communities in the gut ecosystem of L. variegatus, and specifically a selective attribute for Campylobacteraceae in the gut tissue. Also, the predictive functional significance of bacterial communities in uniquely compartmentalized gut ecosystems of L. variegatus has been described.